Enhanced piezoelectric response of hybrid biodegradable 3D poly(3-hydroxybutyrate) scaffolds coated with hydrothermally deposited ZnO for biomedical applications. (August 2019) - Zviagin, Andrei S.; Chernozem, Roman V.; Surmeneva, Maria A.; Pyeon, Myeongwhun; Frank, Michael; Ludwig, Tim; Tutacz, Peter; Ivanov, Yurii F.; Mathur, Sanjay; Surmenev, Roman A.
Graphical abstract: Highlights: Fibrous piezoelectric poly(3-hydroxybutyrate) (PHB) scaffolds were fabricated. Zinc oxide (ZnO) coating was deposited via hydrothermal deposition. d33 coefficient for PHB scaffolds with ZnO coating is substantially increased. ZnO rod-like nanostructured surface improved the wettability of PHB scaffolds. Abstract: Fibrous scaffolds based on biodegradable piezoelectric poly(3-hydroxybutyrate) (PHB) polymers were fabricated via electrospinning. Hydrothermal deposition of zinc oxide (ZnO) on the surfaces of fibrous PHB scaffolds resulted in a homogeneous ZnO layer that grew conformally on the porous polymeric scaffold. X-ray photoelectron spectroscopy (XPS) and X-ray diffraction (XRD) results confirmed the formation of a hexagonal wurtzite crystal structure of ZnO on the PHB fibres. XRD patterns, TEM and EDS analysis revealed a bimodal morphology with rod-like nanostructures that grew preferentially along the c -axis as well as nanoparticles that grew randomly. The piezoelectric charge coefficient d33 for pristine PHB scaffolds was 2.9 ± 0.1 pC⋅N −1, whereas after ZnO deposition, it substantially increased to 13.7 ± 1.6 pC⋅N −1 . Moreover, the output surface electrical potential of PHB scaffolds after ZnO deposition also substantially increased from 0.58 ± 0.02 to 0.88 ± 0.04 V, showing enhanced electromechanical coupling in the piezoelectric nanocomposites. The output surface electric potential for ZnO-coated PHB scaffolds was stable within 1200 loading cycles. In addition, the ZnO rod-like nanostructured surface improved the wettability of PHB fibrous scaffolds, demonstrating synergy between the ceramic and polymeric phases in PHB/ZnO composites. Therefore, the hybrid biodegradable piezoelectric scaffolds reported in the present study are potentially useful for biomedical applications, where both improved piezoelectric response and surface wettability are required.